Dynamic linkages among ASEAN-5 emerging stock markets - Abd. Majid, M. Shabri; Meera, Ahamed Kameel Mydin; Omar, MOhd. Azmi; Abdul Aziz, Hassanuddeen (Emerald Group Publishing Limited, 2009)
Purpose – The purpose of this paper is to empirically explore market integration among five selected Association of Southeast Asian Nations (ASEAN) emerging markets (Malaysia, Thailand, Indonesia, the Philippines and Singapore) during the pre- and post-1997 financial crisis periods.